2018
DOI: 10.1002/jssc.201800817
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of CE‐MS for protein and peptide analysis

Abstract: The review is focused on the latest developments in the analysis of proteins and peptides by capillary electrophoresis techniques coupled to mass spectrometry. First, the methodology and instrumentation are overviewed. In this section, recent progress in capillary electrophoresis with mass spectrometry interfaces and capillary electrophoresis with matrix‐assisted laser desorption/ionization is mentioned, as well as separation tasks. The second part is devoted to applications—mainly bottom‐up and top‐down prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 79 publications
(107 reference statements)
0
30
0
1
Order By: Relevance
“…Both, IEF and zone electrophoresis in CE format (CIEF and CZE) have been successfully combined with MS (CE–MS) for peptide and protein analysis . Technological advancements in instrumentation, coupling to mass spectrometer and improvements in separation performance have accompanied this development . Even though nanoLC–MS is still the most commonly used analysis platform for advanced proteomics , several studies have demonstrated that combination of nanoLC–MS and CE–MS methods increase the number of identified proteins as they are orthogonal and provide complementary results .…”
Section: Introductionmentioning
confidence: 99%
“…Both, IEF and zone electrophoresis in CE format (CIEF and CZE) have been successfully combined with MS (CE–MS) for peptide and protein analysis . Technological advancements in instrumentation, coupling to mass spectrometer and improvements in separation performance have accompanied this development . Even though nanoLC–MS is still the most commonly used analysis platform for advanced proteomics , several studies have demonstrated that combination of nanoLC–MS and CE–MS methods increase the number of identified proteins as they are orthogonal and provide complementary results .…”
Section: Introductionmentioning
confidence: 99%
“…It is well suited to highly charged polar metabolites such as organics acids, nucleotides, peptides and their conjugates. It is coupled to MS instruments using electrospray ionisation ( 27 ) . For high-throughput techniques where it is desirable to have low run time per sample direct infusion MS is often employed.…”
Section: Metabolomics: Role In Biomarker Discoverymentioning
confidence: 99%
“…Other 80 databases include MyCompoundID, a library of 8,021 endogenous human metabolites with 10, 583,901 predicted products of these metabolites nucleotides, peptides and their conjugates. It is coupled to MS instruments using electrospray 114 ionisation (ESI) (27) . For high through-put techniques where it is desirable to have low run 115 time per sample direct infusion mass spectrometry (DIMS) is often employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Son aşamada ise MS yöntemi ile bu proteinlerin kütleleri saptanmakta ve kesin ve doğru olarak proteinlerin tek tek tanımlanması gerçekleştirilmektedir. 3,14 Örnek içerisinde az miktarda bulunan ama belirteç (marker) olabilecek proteinlerin ayrımı için çok hassas bir çalışma gerekmektedir. Proteomik teknolojisine bu proteinlerin tanımlanması, hastalığın gelişimi ile ilgisi ve bu verilerin bilgi bankalarında toplanarak değerlendirilmesi ve normal biyolojik süreçler ile hastalıkların altında yatan mekanizmaların tanımlanması amaçlanmaktadır.…”
Section: Proteomi̇k Anali̇zlerunclassified